Linkages Between Knowledge Management Process and Corporate Sustainable Performance of Chinese Small and Medium Enterprises: Mediating Role of Frugal Innovation - Kun, Ma (Frontiers in Psychology, 2022)
In the contemporary world, frugal innovation (FI) is the most discussed area to enhance corporate sustainable performance (CSP) in manufacturing firms. The knowledge management process (KMP) is also a key determinant of FI. Existing literature is limited to knowledge management (KM) and its impact on CSP. This study aims to determine the effect of the KMP (acquisition, dissemination, and application) on sustainable corporate performance with the association of FI. The survey method was used to collect data from 356 small and medium enterprises (SMEs) in China. Structure equation modeling was applied to obtain the results of collected data. Results show that all three dimensions of KM have a significant impact on CSP. Furthermore, FI also has a significant and positive impact on CSP. Results further show that FI partially mediates the relationship of the knowledge dissemination, knowledge application and sustainable corporate performance but no mediation role FI was found between knowledge acquisition and CSP. The findings of this study will provide useful insights for experts and manufacturers. It will help to understand the role of KM in their organizational behavior by being an economical manufacturing process. This study underscored the importance of the KMP to policymakers. In countries such as China that have global orders, KM is an essential determinant of FI. KM is a tool used to achieve CSP goals inside and outside of an enterprise, thus the development firms need to focus on KM.